Gastroprotective Effect of Combinations of Cincau Leaves and Mangosteen Peel on Ethanol-Induced Gastric Damage - Wahyu Widyaningsih; Eka Novyyanti Sary; Dessy Nur Halimah; Wa Ode Miftahul Jannah (Majalah Obat Tradisional, 2018)
Gastric ulcer is still a health problem in Indonesia. The leaves of cincau (Cyclea barbata Miers) and mangosteen peel (Garcinia mangostana Linn) have been investigated to have gastroprotective effects. This study aims to determine the effect of gastroprotector from the combination of Cincau leaves and mangosteen peel. This study used the post test only control group design. Wistar male rats were divided into 6 groups. Group I was a healthy control group and the second group was an untreated negative control. Group III is positive group treated with Ranitidine (0.016 g / kg BW). Groups IV, V, and VI were given green leaves of cincau (13.5 g / kg BW), mangosteen peel (25 g / kg BW) and 1: 1 combination. Treatment was performed for 14 days. On day 14 1 hour after treatment, all groups (except group I) were given 96% oral ethanol induction at a dose of 5 g / kg BW. On the 15th day the animals were sacrificed by means of anesthesia using chloroform. The area of the tukak is calculated by ImageJ and then calculates the index parameters of the ulcer and the protection ratio. The stomach is made of a hitopathologic preparation with Hematoxylin and Eosin (HE) and Immunohistochemistry (IHC) preparations to observe COX-2 expression. The index data of ulcer, protection ratio, gastric mucosal damage score and number of cells expressing COX-2 were statistically analyzed by SPSS program. The results showed that the combination of green leaves and mangosteen leaf ratio of 1: 1 had a gastroprotective effect by inhibiting the gastric induced index, increasing the ratio of protection, reducing total mucosal damage and inhibiting the expression of COX-2 protein in rat stomach cells significantly (p <0 , 05).  Giving combination of Cincau leaf and mangosteen peal  of 1: 1 able to give gastroprotective effect.